PERAN CORPORATE GOVERNANCE DALAM MEMEDIASI PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Novianti, Nunuk; Wijaya, Indra; Pinory, Clara Mayvinestania Sabrina (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the role of corporate governance (CG) in mediating the influence of financial performance and company size on company value in the banking sector in Indonesia. The research method uses a quantitative approach with an explanatory design, involving secondary data from the annual reports of banking companies listed on IDX for the period 2018–2023. Financial performance variables were measured using ROI, ROE, and total assets; company size was measured through total sales; company value was proxied by market capitalization; while CG was measured through institutional ownership, proportion of independent commissioners, number of commissioners, audit committee, and external audit quality. Data analysis was performed using SEM-PLS. The results show that financial performance and company size have a significant positive effect on company value, both directly and through the mediating role of CG. CG is proven to strengthen the relationship between financial performance and company size with company value, indicating that good governance enhances the credibility and accountability of companies in the eyes of investors. In addition, the direct effect of CG on company value is also proven to be significant, emphasizing the importance of governance practices in increasing company market value. This study contributes theoretically to expanding the literature on the mediating role of CG, while also providing practical implications for banking management to strengthen corporate governance as a strategy for long-term value enhancement.